Excitation of Λ - type three Level System by Pulsed Radiation as a Model of Radiology Tissue Response - Saddam Flayeh Haddawi (Journal of Global Pharma Technology, 2017)
In several biomedical applications, it is desirable to transfer an electron in an atom from one energy level to another. This may be a direct transfer, involving only two atomic levels, or may involve some intermediate levels which the electron must pass through before coming to its final state. The model dealt with here incorporates one such intermediate level, and so we consider three atomic levels in all. Also, our model allows for the possible loss of the electron, via collisional excitation, spontaneous emission, or some other process. We have to de ne a parameter, in units of frequency, which is proportional to the loss rate. The purpose of the thesis is description of the interaction of a three level with pulsed radiation in the Λ scheme. And also we will consider the scheme of excitation whereas two neatly diverged long-term stayed ground states  and, are connected by two nearly resonant laser fields to a third distant short lived state b.